The association of coital incontinence with clinical factors and single voiding cycle ambulatory urodynamic monitoring findings in women - Çetinkaya, Şerife Esra; Seval, Mehmet Murat; Varlı, Bulut; Dökmeci, Fulya (Frontiers in Medicine, 2023)
Introduction Coital incontinence (CI) is a frequent problem in women with urinary incontinence (UI) with significant impact on female sexuality and quality of life. The underlying mechanism is controversial; it has been known that CI is associated with both stress urinary incontinence (SUI) and detrusor overactivity (DO). However, recently it has been reported that CI is mainly related with SUI and urethral incompetence, but not with DO. Ambulatory urodynamic monitoring (AUM) has been shown to be a sensitive tool for the detection of DO. The aim of this study was to investigate the clinical risk factors for CI and the association of CI with urodynamic diagnoses at single voiding cycle AUM. Methods Records of sexually active women with urinary incontinence attending the urogynaecology unit of a university hospital, who completed the PISQ-12 were reviewed retrospectively (n = 1,005). Patients were grouped using the 6th question; patients answering “never” to this question were considered as continent during coitus (n = 591) and patients reporting any urinary leakage at coitus were considered to have CI (n = 414). Demographics, clinical examination findings, incontinence severity measured by the Sandvik Incontinence Severity Index, scores of Turkish validated questionnaires (PFDI-20, IIQ-7, OAB-V8, and PISQ-12) and single voiding cycle AUM findings were compared, and univariate and multivariate logistic regression analyses were performed. Results Among all sexually active women with UI, 41.2% had CI; UI was more severe, symptom bother was higher, related quality of life (p < 0.001) and sexual function were worse (≤0.018) in these women. Younger age (OR 0.967, p < 0.001), history of vaginal delivery (OR 2.127, p = 0.019), smoking (OR 1.490, p = 0.041), postural UI (OR 2.012, p = 0.001), positive cough stress test (OR 2.193, p < 0.001), and positive SEST (OR 1.756, p = 0.01) were found as independent clinical factors associated with CI. Urodynamic SUI (OR 2.168, p = 0.001) and MUI (OR 1.874, p = 0.002) were found as significant and independent urodynamic diagnoses associated with CI, whereas no association was found with DO or UUI. Conclusion Both clinical and AUM findings supported that CI is a more severe form of UI that it is mainly related with SUI and urethral incompetence, but not with UUI or DO.